Journalism in the 21st Century World – Tackling Challenges - Bora, Abhijit (Richtmann Publishing, 2012)
With the advent of internet and digitized formats of communication, journalism has been going through a lot ofchallenges over the last about one-and-a-half decade in an unprecedented situation in which the very concepts of the disciplineare undergoing lot of changes. The challenges are manifold - from citizen journalism to free flow of information and newsthrough the internet, emergence of social networking sites (SNSs) to a large extent are posing newer aspects in front of the fieldof journalism. This paper would endeavour to examine how these developments are facilitating a better flow of informationdissemination to the masses and at the same time creating problems of ascertaining authenticity, journalistic practice without thebenefits of trained human resources. This analysis has been necessitated as the availability of so many virtual digital outletshave facilitated a better flow of information making it highly difficult to hoodwink the masses by deliberately passing on wronginformation. Yet, this uncontrolled flow of information at the same time is also posing serious questions of finding out whetherthe sources are ‘reliable' or not. Also, how much filtering we need to carry out to find out what portion of the information availablefrom the blogs and SNSs are authentic and free from propaganda or personal opinion about an event. Further, this paper wouldalso like to analyze how much of the censorship restrictions in place in many ‘developing nations' including India actually holdsgood in today's media situation where practically everything is freely available through the virtual communication mode.